Antara Profesi, Kompetensi Dan Tugas Kependidikan Seorang Guru - Mu'ammaroh, Nurul lail Rosyidatul (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
Experts of education introduce various theory of learning, so that learning can run effective and effiient, and it is no needs many times. In fact, there is no any theory that shows strategy of learning completely. There are many factors that must be considered, both of internal and external factors. The most inflential of external factors is teacher. Whetherstudents able to receive material well or not is inflenced by teacher. At home, the responsibility of student in the hand of parents, but at school the responsibility of student taken by teacher. In the daily activity, society put high expectation to teacher, since they want their children experience positive -constructive changes.Keywords: profession, competence, teacher.